1976
DOI: 10.1128/jvi.17.1.204-211.1976
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin-Like Structures in Polyoma Virus and Simian Virus 40 Lytic Cycle

Abstract: Nucleoprotein complexes containing viral DNA and cellular histones were extracted from nuclei of permissive cells infected with polyoma virus or simian virus 40 (SV40) and examined by electron microscopy. Polyoma and SV40 nucleoprotein complexes are almost identical. They appear as relaxed circular molecules consisting of 20 to 21 globular particles interconnected by thin filaments. Their contour length in 0.02 M salt is 2.7 times shorter than that of viral DNA form I obtained after dissociation of the protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
49
0

Year Published

1977
1977
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 161 publications
(58 citation statements)
references
References 31 publications
(34 reference statements)
9
49
0
Order By: Relevance
“…An average of 23 beads per ring with a mean diameter of 100 nm has been determined on the 5.2 kb long DNA circle. The compaction ratio of 2.8 in this extended configuration is in good agreement with values determined for SV40 minichromosomes under similar spreading conditions (Griffith, 1975;Cremisi et al, 1976). The lower magnification in Figure Sc gives a representative overview of several assembled DNA molecules, and demonstrates the overall dense packaging of the DNA into nucleosomes.…”
Section: Nucleosome Assembly Activity Of the Purified Histone Complexessupporting
confidence: 86%
“…An average of 23 beads per ring with a mean diameter of 100 nm has been determined on the 5.2 kb long DNA circle. The compaction ratio of 2.8 in this extended configuration is in good agreement with values determined for SV40 minichromosomes under similar spreading conditions (Griffith, 1975;Cremisi et al, 1976). The lower magnification in Figure Sc gives a representative overview of several assembled DNA molecules, and demonstrates the overall dense packaging of the DNA into nucleosomes.…”
Section: Nucleosome Assembly Activity Of the Purified Histone Complexessupporting
confidence: 86%
“…This is the first structural description of such a structure in virus-infected plants. The structure is similar to those of SV40 DNA (Griffith, 1975;Bellard et al, 1976) and polyoma minichromosomes (Cremisi et al, 1976). Our results are in good agreement with those obtained by micrococcal nuclease digestion (Olszewski et al, 1982).…”
Section: Discussionsupporting
confidence: 88%
“…In these respects the SV40 chromatin was similar to chromatin isolated from a variety of mammalian cells (8). We assume that the DNA regions inaccessible to extensive staphylococcal nuclease digestion (6) are contained in the nucleohistone complexes (nucleosomes or v-bodies) seen by electron microscopy (9,12).…”
Section: Discussionmentioning
confidence: 80%
“…It has been demonstrated that the histones of SV40 chromatin isolated from infected cells (9,12) or from visions (5) are condensed into 21 spherical units or v-bodies. It is presumably these structures that result in the failure of staphylococcal nuclease to digest completely all ofthe DNA ofchromatin.…”
mentioning
confidence: 99%